Larval necrophilia: The odd life cycle of a pandeid hydrozoan in the Weddell Sea shelf - Piraino, Stefano; De Vito, Doris; Bouillon, Jean; Boero, F. (2003)
Colonies of an athecate hydroid were found at six stations in the high Antarctic (Weddell Sea) growing on dead specimens of Flabelligera mundata (Annelida, Polychaeta). All living specimens of F. mundata at the same stations were free of epibionts. Transplantation experiments showed that hydropolyps did not produce stolons on substrates other than the epidermal jelly coat and chetae of dead F. mundata specimens. The largest colonies (> 1,000 polyps) producing medusa buds were cultured until medusa liberation: growth of medusae was then surveyed for the next 5 weeks, but development of adult features was extremely slow. Young medusae were ascribed to the suborder Pandeida by the presence of two main characters, namely (1) hollow marginal tentacles, and (2) a mouth with four simple lips. Considering polyp and young medusa features, this species is acknowledged as newly recorded for the Southern Ocean, and assigned to the genus Neoturris (Hydroidomedusae, Pandeidae). SCOPUS: ar.j info:eu-repo/semantics/published